Mycobacterium appelbergii sp. nov., a Novel Species Isolated from a Drinking Water Fountain in a Rural Community - Inês Cravo Roxo; Susana Alarico; Ana Fonseca; Daniela Machado; Ana Maranha; Igor Tiago; Raquel Duarte; Nuno Empadinhas (Microorganisms, 2025)
Three isolates of a novel, rapidly growing, non-pigmented Mycobacterium species were recovered from the water and runoff of a public fountain in a rural village in central Portugal, formerly used by the local population as a source of drinking water and not accessible to animals. High-quality draft genome sequencing, in silico DNA–DNA hybridization, and phylogenetic analyses confirmed that isolates 21AC1T, 21AC14, and 21AC21 represent a previously undescribed species within the genus Mycobacterium, forming a distinct phylogenetic lineage closely related to Mycobacterium wolinskyi, Mycobacterium goodii and Mycobacterium smegmatis. MALDI-TOF MS analysis of the type strain 21AC1T revealed a unique spectral profile. A comprehensive polyphasic characterization was performed, including chemotaxonomic analyses of fatty acid and mycolic acid composition, as well as an extensive biochemical characterization. Their susceptibility to 12 antimicrobials was also assessed. The identification and characterization of novel nontuberculous mycobacteria species are of increasing environmental and clinical relevance, as infections by these opportunistic pathogens are on the rise globally. Based on our findings, we propose that isolates 21AC1T, 21AC14, and 21AC21 represent a novel species, for which we propose the name Mycobacterium appelbergii sp. nov., with the type strain designated as 21AC1T (=BCCM/ITM 501212 = DSM 113570) and the additional two strains as 21AC14 (=BCCM/ITM 501447 = DSM 118402) and 21AC21 (=BCCM/ITM 501448 = DSM 118403).